Materia-autore = Author-matter - Marini, Sara (Vesper, 2020)
The etymology of the word "author," which derives from the root of the Latin verb "augere" ("to increase"), refers to an act of creation or augmentation. As such, the word is essentially a call for expanding the pre-existing. Roland Barthes declared in his famous essay that the author is dead as "a modern figure, a product of our society." Fifty years later, the post-anthropocentric perspective of contemporary thinking and designing in the 21st century seems to emphasise the total overcoming of the author's person. But is that really the case? This instalment of "Vesper" explores the implications for authorship in our time.